Efficiency of Fertilizing Maize Plants Through the Application of Slow Release NPK Tablet Fertilizer with Biofertilizer - Novianti, F.; Syaiful, S. A.; Dachlan, A.; Fadhli, N. (Indonesian Journal of Agricultural Research, 2023)
Inefficiencies in fertilization practices have become a substantial issue within current agricultural techniques. The inappropriate use of fertilizers can negatively impact both crop productivity and soil fertility. The aim of this research is to identify the efficiency of utilizing slow-release NPK tablet fertilizers supplemented with biofertilizers in maize crops. The experimental design incorporated a randomized complete block design (RCBD) consisting of nine combinations of fertilizer dosages between NPK tablet fertilizers and biofertilizers. The efficiency of fertilizer use can be seen from the RAE value of more than 100% shown by the NPK Tablet treatment which requires only one application compared to the recommended fertilizer, urea, and NPK Phonska which requires twice applications. Furthermore, optimization of the application of biofertilizer can be seen in the RSE value of more than 100% shown in the application of LBA biofertilizer together with NPK Tablets so that the application of biofertilizer is considered capable of increasing the efficiency of using inorganic fertilizers such as NPK Tablets.